Cascading reaction of arginase and urease on a graphene-based FET for ultrasensitive, real-time detection of arginine - Berninger, Teresa (2018)
Herein, a biosensor based on a reduced graphene oxide field effect transistor (rGO-FET) functionalized with the cascading enzymes arginase and urease was developed for the detection of L-arginine. Arginase and urease were immobilized on the rGO-FET sensing surface via electrostatic layer-by-layer assembly using polyethylenimine (PEI) as cationic building block. The signal transduction mechanism is based on the ability of the cascading enzymes to selectively perform chemical transformations and prompt local pH changes, that are sensitively detected by the rGO-FET. In the presence of L-arginine, the transistors modified with (PEI/urease(arginase)) multilayers showed a shift in the Dirac point due to the change in the local pH close to the graphene surface, produced by the catalyzed urea hydrolysis. The transistors were able to monitor L-arginine in the 10–1000 μM linear range with a LOD of 10 μM, displaying a fast response and a good long-term stability. The sensor showed stereospecificity and high selectivity in the presence of non-target amino acids. Taking into account the label-free, real-time measurement capabilities and the easily quantifiable, electronic output signal, this biosensor offers advantages over state-of-the-art L-arginine detection methods.